IMPLEMENTATION OF METHODS OF LOCO-REGIONAL ANESTHESIA IN DENTAL SURGERY - Oana-Elena Ciurcanu; Doriana Agop Forna; Cristina Popa; Mihaela Monica Scutariu (Romanian Society of Oral Rehabilitation, 2018)
Even the minor surgery, anesthesia, by interrupting the normal course of life, bringing the patient into a state of dependence on the attending physician, the medical staff, the drugs, the preoccupation with the type of anesthesia, the duration and the course of the intervention, its success or complications, logically inspires a sense of fear. So, it is normal for the patient to be concerned about the method, technique and quality of anesthesia and surgery, the possibility of deficiency in the installation or the duration of anesthesia that could cause pain during the intervention or immediately afterwards. The problem of dento-alveolar surgery interventions in a dental practice ward presents multiple aspects and needs, in the context of increasing dental care both in private or state practice. Loco-regional anesthesia is the method by which chemical, physical or electric current are used to temporarily insensify the anatomical region on which it is intervening, while keeping the consciousness intact; in this kind of anesthesia only painful sensitivity is abolished, the thermal, tactile, and pressure sensitivities being retained, referred to by the American authors as "loco-regional analgesia". In recent years new intraosseous anesthesia techniques have been developed and introduced on the market: the Stabident system; X-type; Quicksleeper; Intraflow; Hypo. With regard to injection methods of anesthetics, computerized electronic systems for the administration of anesthetics have appeared on the market. Intraoral application sites influence the time of installation and the duration of anesthesia after application of the local anesthetic.